Interaction of Isoniazid with Al(OH)3: A DFT Study - Akalin, E.; Akyuz, S.; Akyuz, T. (Asian Journal of Chemistry, 2010)
The harmonic and anharmonic vibrational wavenumbers of isoniazid (INH) interacting with Al(OH)3 through the ring nitrogen have been calculated by using the density functional theory (DFT) method with Becke3Lyp functional and 6-31++G(d,p) basis set, in order to investigate coordination through the ring nitrogen effects on INH vibrational wavenumbers. The total energy distributions (TED) of the vibrational modes were calculated by using scaled quantum mechanical (SQM) analysis. Fundamentals were characterized by their total energy distribu-tions. Coordination sensitive modes of isoniazid were determined.